Issues of Equity and Access in State-Designed Promise Programs: A Critical Analysis of Free Community College Legislative Frameworks (Higher Education Politics and Economics, 2025)
Tuition-free college programs, often referred to as promise programs, have proliferated across the country. While previous literature on promise programs has shown positive results for the students who receive these scholarships, it has failed to account for program design and administrative features of the program (such as income caps, age, time eligibility, merit, etc.) and what consequences these program design choices have on equitable student outcomes. This critical policy analysis adds to the emerging literature on promise program design by analyzing 202 tuition-free community college legislation proposed at the state level. Results show that tuition-free community college legislative frameworks are proposed with various eligibility, application, funding, and administrative requirements and that program design elements could exacerbate achievement gaps for historically underrepresented students.